Cementerio - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1987)
SPANISH: Cementerio de San Juan en 1987, ubicado en el distrito de San Juan bautista
ENGLISH: San Juan Cemetery in 1987, located in the district of San Juan Bautista.

SPANISH: Cementerio de San Juan en 1987, ubicado en el distrito de San Juan bautista
ENGLISH: San Juan Cemetery in 1987, located in the district of San Juan Bautista.
Cemetery
Keywords: cementerio|~|Iquitos (Perú)